Conventional endotracheal tubes versus polymer-coated tubes in ventilator-associated pneumonia development: A systematic review and meta-analysis - Oscar Inácio de Mendonça Bisneto; Luanna Paula Garcez de Carvalho Feitoza; Larissa Calixto Hespanhol; Sávio Benvindo Ferreira; Caroline Serafim Dagostin; Roberto Augusto Mazetto Silva Vieira; Lucas Alencar Queiroz; Lucas Chen; Taniela Marli Bes; Ho Yeh Li (Heliyon, 2025)
Introduction: Endotracheal tubes (ETT) are used in patients who require ventilatory support. Colonization of ETTs by microorganisms is associated with developing ventilator-associated pneumonia (VAP). Thus, this meta-analysis aims to compare conventional endotracheal tubes with those made using materials designed to prevent colonization. Methods: This analysis was conducted according to the PRISMA guidelines. During May 2024, we searched multiple databases (PubMed, Cochrane and Embase) for randomized controlled trials (RCT) comparing the incidence of ventilator-associated pneumonia between conventional and coated tubes. Studies with patients with less than 48 h of intubation were excluded. Our primary endpoint was the incidence of VAP in patients intubated with either conventional or coated endotracheal tubes. Statistical analysis was performed using Review Manager Software, and a The Mantel-Haenszel test was performed using a random effects model, and risk ratios (RR) were calculated for binary outcomes. Subgroup analyses were conducted using a fixed effects model when heterogeneity was low. Risk assessment was carried out using the Risk of Bias 2 tool. Results: Our search identified 6 RCTs eligible in our inclusion criteria, enrolling 2680 patients, with 1361 (50,78 %) undergoing intubation using a polymer-coated tube. The statistical data indicated that coated endotracheal tubes perform better in preventing pneumonia than conventional tubes (RR 0.57 Cl 95 % 0.45–0.90; p < 0.001; I2 0 %). Additionally, conventional tubes were also associated with higher bacterial colonization (47.02 CI 95 % 26.88–68.18; p < 0.01; I2 81 %) compared to coated tubes. Conclusions: These findings indicate that utilizing a silver-coated endotracheal tube for intubation is more efficacious than conventional tubes, presenting it as a strategy to combat ventilator-associated pneumonia.